Development of new bioactive molecules to treat breast and lung cancer with natural myricetin and its derivatives: A computational and SAR approach - Akash, Shopnil; Kumer, Ajoy; Rahman, Md. Mominur; Emran, Talha Bin; Sharma, Rohit; Singla, Rajeev K.; Alhumaydhi, Fahad A.; Khandaker, Mayeen Uddin; Park, Moon Nyeo; Idris, Abubakr M.; Wilairatana, Polrat; Kim, Bonglee (Frontiers in Cellular and Infection Microbiology, 2022)
Each biopharmaceutical research and new drug development investigation is targeted at discovering novel and potent medications for managing specific ailments. So, to discover and develop new potent medication, it should be performed sequentially or step by step. This is since drug development is lengthy and risky work that requires significant money, resources, and labor. Breast and Lung cancer are complicit in the death of millions of people throughout the globe each year, according to the report of the World Health Organization, and it has been creating a global public threat worldwide. Although, the global medical sector is developed and updated day by day. But not, any proper treatment is possible to find till now. So, this research has been conducted to find a new bioactive molecule to treat Breast and lung cancer with natural Myricetin and its derivatives using by latest and most authentic computer-aided drug design approaches. At the beginning of this study, the biological pass prediction spectrum was calculated to select the target protein. It is noted that the probability of active (Pa) score is better than antineoplastic (Pa 0.788 – 0.938) in comparison with antiviral (Pa0.236 – 0.343), antibacterial (0.274 – 0.421), and antifungal (Pa, 0.226 – 0.508). So, the cancerous proteins such as Breast and Lung Cancer have been picked up and continued the computational investigation. Furthermore, the docking score finding was observed at -7.3 kcal/mole to -10.4 kcal/mole for Breast cancer (standard epirubicin hydrochloride -8.3 kcal/mol), whereas the Lung cancer scored -8.2 kcal/mole to -9.6 kcal/mole (standard carboplatin -5.5 kcal/mole). The docking score is the primary concern, revealing that myricetin derivatives have better docking scores than standard chemotherapeutic agents Epirubicin hydrochloride and carboplatin. Finally, drug-likeness, ADME, and toxicity prediction are satisfied by this investigation, and it is noted that all the derivatives are highly soluble in the water medium, while they are totally free from AMES toxicity, Hepatotoxicity, and Skin Sensitization excluding only ligand 01 and 07. So, we proposed that the natural myricetin derivatives could be a better inhibitor for treating Breast and Lung cancer.